Guidelines on the prevention of foot ulcers in persons with diabetes (IWGDF 2019 update). (16th March 2020) - Bus, Sicco A.; Lavery, Lawrence A.; Monteiro‐Soares, Matilde; Rasmussen, Anne; Raspovic, Anita; Sacco, Isabel C.N.; van Netten, Jaap J.
Abstract: The International Working Group on the Diabetic Foot (IWGDF) has published evidence‐based guidelines on the prevention and management of diabetic foot disease since 1999. This guideline is on the prevention of foot ulceration in persons with diabetes and updates the 2015 IWGDF prevention guideline. We followed the GRADE methodology to devise clinical questions and critically important outcomes in the PICO format, to conduct a systematic review of the medical‐scientific literature, and to write recommendations and their rationale. The recommendations are based on the quality of evidence found in the systematic review, expert opinion where evidence was not available, and a weighing of the benefits and harms, patient preferences, feasibility and applicability, and costs related to the intervention. We recommend to screen a person at very low risk for ulceration annually for loss of protective sensation and peripheral artery disease and persons at higher risk at higher frequencies for additional risk factors. For preventing a foot ulcer, educate the at‐risk patient about appropriate foot self‐care and treat any pre‐ulcerative sign on the foot. Instruct moderate‐to‐high risk patients to wear accommodative properly fitting therapeutic footwear, and consider instructing them to monitor foot skin temperature. Prescribe therapeutic footwear that has a demonstrated plantar pressure relieving effect during walking to prevent plantar foot ulcer recurrence. In patients that fail non‐surgical treatment for an active or imminent ulcer, consider surgical intervention; we suggest not to use a nerve decompression procedure. Provide integrated foot care for high‐risk patients to prevent ulcer recurrence. Following these recommendations will help health care professionals to provide better care for persons with diabetes at risk of foot ulceration, to increase the number of ulcer‐free days, and to reduce the patient and health care burden of diabetic foot disease.